Use of metabolites of therapeutic Lactic acid bacteria to inhibit four species veterinary pathogenic bacteria: Ali H. A . Hamid , S.C. Abood , H.R.Al sharefe - Hamid, Ali H. A . (The Iraqi Journal of Veterinary Medicine, 2005)
This study aimed to detect metabolites inhibition activity for three therapeuticLactic acid bacteria Lactobacillus acidophilus (Lb. acid.) , Lactobacillus reuteri(Lb. reut.) and Bifidobacterium ssp. (Bif.) which were grown in whole milk andMan Reqosa and Sharp (MRS) broth as single or double (Lb. acid. + Bif.) ormixed (Lb. reut + Bif. + Lb. acid) culture Cell Free Extract (CFE) of theseculture which contained their metabolites of Lactic acid bacteria (exclusion Lb.reut.) showed good inhibition against four species of pathogenic Escherichiacoli ; Salmonella typhimurium ; Proteus volgaris and Staphylococcus aureus.inhibition activity against E. coli culture showed that 72 hours was the bestincubation time for Lactic acid bacteria to produce more metabolite with bestinhibition activity. Metabolite (CFE) of Lb. Acid culture grown in milk andMRS broth showed the best inhibition activity against all of Gram Positive andGram negative test bacteria with over all inhibition zone diameter was 14.6 and15.3 mm for milk and MRS broth supernatant respectively and this activityremained for more than one week as inhibition zone diameter were 13.4 and14.5 mm for supernatant of milk and MRS respectively.